2015
DOI: 10.1038/jcbfm.2014.225
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of [11C]yohimbine Binding to α2 Adrenoceptors in Rat Brain in vivo

Abstract: We quantified the binding potentials (BPND) of [11C]yohimbine binding in rat brain to alpha-2 adrenoceptors to evaluate [11C]yohimbine as an in vivo marker of noradrenergic neurotransmission and to examine its sensitivity to the level of noradrenaline. Dual [11C]yohimbine dynamic positron emission tomography (PET) recordings were applied to five Sprague Dawley rats at baseline, followed by acute amphetamine administration (2 mg/kg) to induce elevation of the endogenous level of noradrenaline. The volume of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Recent studies have focused on PET radiotracers for α2-adrenoreceptors such as [ 11 C]yohimbine [144] and [ 11 C]ORM-13070 [145]. [ 11 C]Yohimbine, for example, has been shown to be a surrogate marker of NA release in rats [146] and pigs [144] by showing a significant decrease in the V T in response to amphetamine challenge. For example, acute amphetamine injection of 2 mg/kg induced a BP ND change of~38 % in rats [146].…”
Section: Quantification Of Neurotransmitter Release In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused on PET radiotracers for α2-adrenoreceptors such as [ 11 C]yohimbine [144] and [ 11 C]ORM-13070 [145]. [ 11 C]Yohimbine, for example, has been shown to be a surrogate marker of NA release in rats [146] and pigs [144] by showing a significant decrease in the V T in response to amphetamine challenge. For example, acute amphetamine injection of 2 mg/kg induced a BP ND change of~38 % in rats [146].…”
Section: Quantification Of Neurotransmitter Release In Rodentsmentioning
confidence: 99%
“…[ 11 C]Yohimbine, for example, has been shown to be a surrogate marker of NA release in rats [146] and pigs [144] by showing a significant decrease in the V T in response to amphetamine challenge. For example, acute amphetamine injection of 2 mg/kg induced a BP ND change of~38 % in rats [146]. However, the quantification of α2-adrenoreceptors and endogenous NA in rodent models with kinetic modeling still remains difficult due to the distribution of the receptors throughout the whole brain, leaving no appropriate reference region.…”
Section: Quantification Of Neurotransmitter Release In Rodentsmentioning
confidence: 99%
“…For quantitative analysis in humans, a metabolite-corrected arterial input function may be required, although the corpus callosum was explored as a potential reference region (Nahimi et al 2015 ). Phan et al ( 2015 ) recently demonstrated that amphetamine also reduced [ 11 C]yohimbine binding in rats (Phan et al 2015 ).…”
Section: Current State Of the Art: Imaging Neurotransmitter Changes Umentioning
confidence: 99%
“…Phan et al ( 2015 ) recently demonstrated that amphetamine also reduced [ 11 C]yohimbine binding in rats (Phan et al 2015 ).…”
Section: Current State Of the Art: Imaging Neurotransmitter Changes Umentioning
confidence: 99%
“…Yohimbine is also a substrate of the p-glycoprotein (p-gp) (a member of the ABC-cassette family of blood brain barrier transporters) in rodents and does not cross into the brain unless the pump is inhibited. After p-gp inhibition, yohimbine can provide useful data in various rodent models [48,30]. Many other tracers also have variable substrate sensitivity to p-gp and other blood brain barrier transporters across different animal species, and this has to be taken into consideration when comparing human and animal model data [61,65].…”
Section: Caveats In Imaging Animal Modelsmentioning
confidence: 99%